2016
DOI: 10.1002/rcm.7558
|View full text |Cite
|
Sign up to set email alerts
|

Use of deuterium labeling by high‐temperature solid‐state hydrogen‐exchange reaction for mass spectrometric analysis of bradykinin biotransformation

Abstract: Quantitative assays demonstrated applicability of the heavy peptide for both sequencing and quantification of generated fragments. Applicability of the HSCIE deuterated peptide for analysis of routes of its degradation has been shown in in vitro experiments. Copyright © 2016 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 51 publications
(132 reference statements)
0
10
1
Order By: Relevance
“…This situation immediately raises the question of which fragments are, in fact, the most likely endogenous peptides formed from BK-(1-9) in vivo. In several earlier studies, BK-(1-8), BK-(1-7) and BK-(1-5) were identified as the major peptide fragments of BK-(1-9) (Murphey et al , 2000;Marshall et al , 2002;Ahmad et al , 2006;Ramirez-Molinaet al , 2006;Kopylov et al , 2016;Semis et al , 2019). In the present work, by monitoring the stable isotope-labelled [Pro 3 ( 13 C 5 ; 15 N)]-BK-(1-9), we were able to detect in vivo production of BK-(1-7) and BK-(1-5), after an infusion of BK-(1-9), thus confirming that these fragments are endogenously produced BK-(1-9) metabolites.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This situation immediately raises the question of which fragments are, in fact, the most likely endogenous peptides formed from BK-(1-9) in vivo. In several earlier studies, BK-(1-8), BK-(1-7) and BK-(1-5) were identified as the major peptide fragments of BK-(1-9) (Murphey et al , 2000;Marshall et al , 2002;Ahmad et al , 2006;Ramirez-Molinaet al , 2006;Kopylov et al , 2016;Semis et al , 2019). In the present work, by monitoring the stable isotope-labelled [Pro 3 ( 13 C 5 ; 15 N)]-BK-(1-9), we were able to detect in vivo production of BK-(1-7) and BK-(1-5), after an infusion of BK-(1-9), thus confirming that these fragments are endogenously produced BK-(1-9) metabolites.…”
Section: Discussionmentioning
confidence: 96%
“…BK-(1-9) is a substrate for carboxypeptidases (e.g., ACE and ACE2), aminopeptidases (e.g., aminopeptidase P) and endopeptidases (e.g., neutral endopeptidase, now neprilysin), thus generating many different cleavage products (Campbell, 2013;Verano-Braga et al , 2020). A general conclusion of BK-(1-9) metabolism is that its major proteolytic fragment is the BK-(1-8), which is acknowledged as the only biologically active BK peptide known to date, together with BK-(1-7) and BK-(1-5) that are regarded as biologically inert fragments (Kopylov et al , 2016;Semis et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…However, we would like to stress that BK-(1-8), BK-(1-7) and BK-(1-5) have been identified as the major BK-(1-9) proteolytic fragments (2,19,23,27,31,41). Given the natural occurrence of these peptides and their biological activity reported in this manuscript, it is likely that BK-(1-7) and BK-(1-5) play important roles in physiological and pathological conditions, which requires extensive research to unravel their particularities.…”
Section: Discussionmentioning
confidence: 99%
“…However, all studies concluded that the fragments derived from BK-(1-9) were devoid of biological activity, except for BK-(1-8) (30, [32][33][34]44). From extensive studies regarding BK-(1-9) proteolysis, it is consensus that BK-(1-8), BK-(1-7) and BK-(1-5) are the major proteolytic fragments, being the latter the most stable fragment in plasma (19,41).…”
Section: Introductionmentioning
confidence: 99%
“…neutral endopeptidase, now neprilysin), thus generating many different cleavage products (Campbell, 2013;Verano-Braga et al, 2020). A general conclusion of BK-(1-9) metabolism is that its major proteolytic fragment is BK-(1-8), which is acknowledged as the only biologically active BK peptide known to date, together with BK-(1-7) and BK-(1-5) that are regarded as biologically inert fragments (Kopylov et al, 2016;Semis et al, 2019). Thus, we present here a re-evaluation of the biological activities exhibited by BK-(1-7) and BK-(1-5), compared with those of the parent nonapeptide BK-(1-9), in a range of in vitro, ex vivo and in vivo systems, using human and rodent models.…”
Section: Introductionmentioning
confidence: 99%